A decision model responding to the refuge request from a ship in need of assistance. (September 2018) - Qi, Zhixin; Zhang, Chunchang; Han, Junsong; Gao, Yali; Xiong, Deqi
Abstract: When a ship in need of assistance has requested a place of refuge with regards to the maritime administration, deciding on the most suitable form of refuge is often both a political and technical problem. To avoid opposition by local communities, a decision model responding to such ship requests is generally established to enable the refuge designation on a case-by-case basis. Within this framework, a step-by-step ranking process is proposed, first selecting indices for potential candidate refuge sites according to the purpose of requesting refuge, with all indices then ordered by pairwise comparison. The weight of each index is determined according to the tone word used for adjacent comparison, and the suitability score for each candidate port obtained. The model is then applied to a hypothetical ship accident in the Bohai Sea in China, which further illustrates the envisaged response process and provides a solution to contemporary maritime administration. Abstract : Highlights: A decision model responding to the ship request is established to enable the refuge designation on a case-by-case basis. The decision framework includes nomination, exclusion and ranking of potential refuge sites. The ranking of candidate refuge sites includes index selection, index ordering by pairwise comparison, index weighting by adjacent comparison, and site scoring. The decision model is applied to a hypothetical ship accident in the Bohai Bay in China.